By lifelong learning conception to higher competitiveness - Plantic, Diana (Ekonomski pregled, 2005)
Assuming that strategic development and competitiveness of a state depend on the quality of primarily its human resources, it is unquestionable that the importance of Croatian educational system and the necessary investments in education quality improvement have to be perceived through the prism of all its forms and structural elements. At the same time informal educational concepts should also be taken into consideration. The more and more popular lifelong learning presents a new development orientation which ensures long-term monitoring of modern market trends. Today's turbulence of global business environment has caused the unconditional acceptance of a continuous educational philosophy for life-time, considered not only in the general context of a society, but also of each organisation and individual. Croatian system of lifelong learning considerably lags behind highly developed countries. Today's modest investments in Croatian education and ineffectiveness of its educational system present a significant obstacle to the future strengthening of Croatian business subject competitiveness as well as the competitiveness of the entire Croatian economy. Reprinted by permission of the Croatian Economics Association